Young scientist and sports : featuring baseball, football, basketball - Barr, George, 1907-; Waltrip, Mildred (New York : Whittlesey House, 1962)
Discusses the rules and play of baseball, football, and basketball as influenced by scientific principles, and describes the athlete's body as a scientific machine.
Keywords: Sports -- Juvenile literature; Sports